Invasive alien plant litter influences larval density, size and survival of Culex spp. - Chiuya, Tatenda; Fèvre, Eric M.; Lutomiah, J.; Mutisya, J.; Mulwa, F.; Chelangat, B.; Muhoro, S.; Olubowa, R.; Junglen, S.; Borgemeister, C. (Nature Research, 2025)
Invasive alien plant (IAP) litter can alter the organic and inorganic content of mosquito breeding sites, influencing their life history traits. In Baringo County, Kenya, there is massive encroachment of Prosopis juliflora and Parthenium hysterophorus into crop and grazing lands. To mimic natural shedding, we set up experimental water containers in the field containing dried plant litter of either Parthenium, Prosopis or Lantana camara, which are invasive and Acacia tortilis which is native to the area. We measured water physicochemical parameters and counted mosquito larvae periodically for 6 weeks. After rearing, we determined survival rates and size of the emergent adults. All the plant treatments had significantly more larvae than the water-only control. Prosopis had the highest number of larvae which was significantly different from Acacia. Water conductivity, total dissolved solids and salinity were highest in Prosopis and Parthenium litter. For both Culex pipiens and Culex vansomereni, adults emerging from Prosopis and Parthenium litter were significantly larger in size compared to those from the other plants. Generally, for the two species, adults from IAPs survived longer than those from Acacia. Our study demonstrates the impact of IAPs on the life history traits of mosquitoes and how they can enhance their vectorial capacity. Mitigating the spread of these plants may reduce mosquito populations and risk of mosquito-borne disease.